Typing Candida albicans oral isolates from human immunodeficiency virus-infected patients by multilocus enzyme electrophoresis and DNA fingerprinting. - Boerlin, P (1996)
A total of 189 Candida albicans isolates have been typed by multilocus enzyme electrophoresis. The results obtained confirm the clonal mode of reproduction of C. albicans. The C. albicans populations found in the oropharynx of human immunodeficiency virus (HIV)-infected patients, in the oropharynx of healthy carriers, or in association with invasive candidiasis could not be distinguished. No clone or group of clones could be associated with the appearance of clinical disorders or with a reduced in vitro susceptibility to the antifungal agent fluconazole. Multiple and sequential oral isolates from 24 HIV-infected patients were also typed by restriction enzyme analysis with the enzymes EcoRI and HinfI and by use of the Ca3 repetitive probe. The results obtained by the combination of all three typing methods show that all but one patient each carried a unique major C. albicans clone in their oropharynx. The 21 patients with sequential isolates had the same C. albicans clones in their throats during recurrent oropharyngeal candidiasis episodes, independently of clinical status or of changes of in vitro susceptibility to fluconazole. Finally, several isolates of the same C. albicans clone found simultaneously in the oropharynx of a patient may present different levels of susceptibility to fluconazole.